Information literacy through resource-based learning: Malaysian teachers’ conception and instructional practices - Yu, Halida; A., Abrizah; Johari Abdullah Sani, Mad Khir; Yu, Halida; Abrizah, A.; Abdullah Sani, Mad Khir Johari (Malaysian Journal of Library and Information Science, 2016)
This paper examines how secondary school teachers in Malaysia conceptualize information literacy, and how this understanding leads to information literacy practices through resource-based learning. Although there have been studies carried out in this area, most of the studies are conducted in western societies with sound exposure to information literacy. This study takes place in a learning environment where information literacy is not a central focus in the school curriculum. It employs a qualitative approach in the form of a case study. Five history subject teachers supervising resourcebased learning history project took part in the study. Data were collected through a series of interviews with the teacher participants to uncover: (a) their conceptions of information literacy; (b) their teaching focus in the project instruction; and (c) the instructional approach employed. Six information literacy conceptions, six information literacy teaching focuses, and four types of information literacy instructional methods are generated from the study. The findings suggest that the teachers’ conceptions of information literacy in Malaysia are quite comparable to those from developed countries. However, the outlooks are more superficial and lack richness and depth. Further findings show that these conceptions influence and shape teachers’ information literacy teaching focuses, as well as their project instructional approaches.